Seniority and Distribution in a Two-Worker Trade Union - Kuhn, Peter; Robert, Jacques (Quarterly Journal of Economics, 1989)
Unlike existing models that rely heavily on assumptions regarding unions' distributional preferences, we present a simple model in which union seniority-layoff rules and rising seniority-wage profiles result from optimal price discrimination against the firm. Surprisingly, even when cash transfers among union members are ruled out, unions' optimal seniority-wage profiles are likely to be completely unaffected by their distributional preferences because of a kink in the utility-possibility frontier. This suggests that the simple technology of price discrimination may play a key role, hitherto unappreciated, in explaining union policies that affect the relative well-being of different union members.